GEOCHEMICAL EXPLORATION FOR GOLD IN DEEP WEATHERED LATERITISED GOSSANS IN THE AMAZON REGION, BRAZIL: A CASE HISTORY OF IGARAPÉ BAHIA DEPOSIT - Costa, M. L.; Angélica, R. S.; Fonseca, L. R. da (Geochimica Brasiliensis, 2011)